Synthesis and characterization of diaza analogues of podophyllotoxin - Basavaraju, Yeriyur Basavaiah; Umesha, Basavaiah (European Journal of Chemistry, 2013)
In an attempt to synthesize the novel diaza analogues of podophyllotoxin (7a-d) in five step reactions. The synthesis of title compounds has been achieved from tetralones, which were formylated with ethylformate; prepared via cyclization with hydrazine hydrate. Furthermore, these newly synthesized compounds were characterized by spectral and elemental analysis data.